2020
DOI: 10.1002/bjs.11490
|View full text |Cite
|
Sign up to set email alerts
|

Closure of the fascial defect during laparoscopic umbilical hernia repair: a randomized clinical trial

Abstract: Background The objective of the study was to analyse patient-reported outcome measures (PROMs), seroma formation, long-term recurrence and chronic pain after closure of the fascial defect in patients undergoing laparoscopic umbilical hernia mesh repair. Methods This was a randomized double-blinded trial in patients undergoing elective laparoscopic umbilical hernia repair comparing sutured closure of the fascial defect before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 32 publications
1
32
1
1
Order By: Relevance
“…Suwa et al [20] revealed that the recurrence rate, incidence rate of seroma formation, and incidence rate of mesh bulging in the IPOM plus technique for ventral and incisional hernias were 0-7.7%, 0-11.4%, and 0%, respectively. Moreover, Christoffersen et al [21] reported that the recurrence rate after 2 years and seroma formation after 30 days were 3-17% and 10-33%, respectively. In the absence of abdominal wall tension during fascial closure, an additional fascial closure technique seems to decrease seroma formation, mesh bulging, and recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Suwa et al [20] revealed that the recurrence rate, incidence rate of seroma formation, and incidence rate of mesh bulging in the IPOM plus technique for ventral and incisional hernias were 0-7.7%, 0-11.4%, and 0%, respectively. Moreover, Christoffersen et al [21] reported that the recurrence rate after 2 years and seroma formation after 30 days were 3-17% and 10-33%, respectively. In the absence of abdominal wall tension during fascial closure, an additional fascial closure technique seems to decrease seroma formation, mesh bulging, and recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Umbilical hernia repair is often conducted as ambulatory surgery requiring early pain control and is therefore a relevant outcome 2,3 . The present study hypothesised that closure of the fascial defect increase tissue tension, and thus, may increase early postoperative pain 1 .…”
mentioning
confidence: 89%
“…Thank you for giving us the opportunity to comment on the correspondence by Dr. Ramakrishna and co‐workers to our recent study 1 .…”
mentioning
confidence: 99%
“…Various procedures have been suggested to reduce seroma formation between the mesh and the sac, but only conventional defect closure seems to reduce postoperative seroma significantly 3 . A recent study 6 reported seroma at the 1-month visit, detected by clinical examination and (if inconclusive) abdominal CT, in 58 per cent of patients who underwent simple IPOM versus 25 per cent of those who had IPOM-plus. It has been hypothesized that the lower incidence of seroma following defect closure is because of decreased dead space in the residual sac.…”
Section: Introductionmentioning
confidence: 97%